2017
DOI: 10.1155/2017/5241012
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Status, Disease Activity, and Endothelial Dysfunction in Early Rheumatoid Arthritis Patients

Abstract: Cardiovascular diseases represent important complications in rheumatoid arthritis (RA) patients, generated by an accelerated atherosclerosis. The aim of this study is represented by the assessment of the correlations between serum levels of vitamin D, disease activity, and endothelial dysfunction in patients with early RA. Material and Methods. The study was performed on a group of 35 patients with early RA and 35 healthy subjects matched for age and gender, as controls. In all studied subjects, the following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 51 publications
1
25
0
2
Order By: Relevance
“…In agreement with these findings, current evidence demonstrates an important reduction in vascular endothelium-dependent vasodilatation, which is correlated with parameters of clinical disease activity [30]. Caraba et al [31] reported similar findings, demonstrating that disease activity is positively correlated with insulin resistance and endothelial dysfunction [31].…”
Section: Rheumatoid Arthritissupporting
confidence: 76%
“…In agreement with these findings, current evidence demonstrates an important reduction in vascular endothelium-dependent vasodilatation, which is correlated with parameters of clinical disease activity [30]. Caraba et al [31] reported similar findings, demonstrating that disease activity is positively correlated with insulin resistance and endothelial dysfunction [31].…”
Section: Rheumatoid Arthritissupporting
confidence: 76%
“…On the contrary, Beyazal et al found no impact of disease duration on vascular function [40]. Caraba et al reported significant associations between low serum levels of vitamin D and disease activity, increased insulin resistance, and endothelial dysfunction (assessed by flow-mediated vasodilation, on brachial artery, using B-mode ultrasonography) in early RA patients with moderate and high disease activity [41]. The relation between EAT and AS has been addressed in studies performed both in the general population, as well as in subgroups of patients with hypertension, cardiovascular disease, post-menopausal women or nonalcoholic fatty liver disease [13,[42][43][44], all reporting significant correlation.…”
Section: Discussionmentioning
confidence: 99%
“…VDR's first evolutionary function was the control of metabolism, in order to support the evolving immune system of ancestral vertebrates with energy [9]. Thus, VDR and its ligand first specialized in the modulation of innate and adaptive immunity, such as fighting against bacterial and viral infections [10,11] and preventing autoimmune diseases, such as multiple sclerosis and rheumatoid arthritis [12,13], before they took on the additional task of regulating bone metabolism. Thus, vitamin D deficiency is causing an increase in bone disease, such as rickets [14], and it may also be one of the reasons for increased vulnerability, particularly in elderly persons, against viral infections, such as the recent coronavirus (COVID-19) outbreak [15].…”
Section: Introductionmentioning
confidence: 99%